2005
DOI: 10.1002/adfm.200500207
|View full text |Cite
|
Sign up to set email alerts
|

Using Self‐Assembling Dipole Molecules to Improve Charge Collection in Molecular Solar Cells

Abstract: Surface modification of indium tin oxide (ITO)‐coated substrates through the use of self‐assembled monolayers (SAMs) of molecules with permanent dipole moments has been used to control the anode work function and device performance in molecular solar cells based on a CuPc:C60 (CuPc: copper phthalocyanine) heterojunction. Use of SAMs increases both the short‐circuit current density (Jsc) and fill factor, increasing the power‐conversion efficiency by up to an order of magnitude. This improvement is attributed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
233
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(241 citation statements)
references
References 25 publications
7
233
0
1
Order By: Relevance
“…Transparent conductive oxides (TCOs) are essential electrode materials for applications in organic electronics, such as organic photovoltaics (OPVs), [1][2][3][4] organic thin-film transistors, 5 organic light-emitting diodes, 6,7 and perovskite solar cells. 8 Understanding and controlling the surface properties of TCO electrodes can improve the performance of these types of devices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transparent conductive oxides (TCOs) are essential electrode materials for applications in organic electronics, such as organic photovoltaics (OPVs), [1][2][3][4] organic thin-film transistors, 5 organic light-emitting diodes, 6,7 and perovskite solar cells. 8 Understanding and controlling the surface properties of TCO electrodes can improve the performance of these types of devices.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement was attributed to a greater short circuit current (J SC ), courtesy of an enhanced interfacial electron-transfer (ET) rate at the anode resulting from a shift in the ITO work function, which lowered the injection barrier between the electrode Fermi level and the CuPc HOMO. 2 Redox-active modifiers offer the possibility of further enhancing the charge-collection efficiency at a TCO/organic interface by serving as a "mediator" layer with a tunable redox potential that can be matched to the relevant charge-transport energy levels. 3,15 Lin et al 15 used redox-active zinc phthalocyanine phosphonic acids (ZnPcPAs) to modify ITO electrodes that were tested as bottom contacts in CuPc/C 60 planar heterojunction solar cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, therefore, two possible explanations for the increase in V oc upon annealing of the nc-PbS layer: It is plausible that the ITO/nc-PbS contact is modified upon removal of the oleic acid ligand, thereby improving alignment between the ITO Fermi level and the relevant transport band in the adjacent nc-PbS. Alternatively, since it is well known that organic adsorbates can affect the work function of inorganic surfaces by modifying the surface potential, 23 it is possible that the offset between the nc-PbS valence band and C 60 LUMO is reduced in the presence of oleic acid ligands, thereby reducing V oc .…”
mentioning
confidence: 99%
“…It has recently been shown that V oc in bilayer organic solar cells is virtually independent of the work function of the hole-extracting electrode. 10 In this case the work functions of the microwave oxygen plasma treated ITO electrode and o-MWCNTs were measured using ultraviolet photoelectron spectroscopy ͑UPS͒ to be ϳ4.4 and ϳ5.0 eV, respectively. Such a small change in V oc would be consistent with this idea.…”
mentioning
confidence: 99%